COMMON ERRORS IN VIETNAMESE-ENGLISH TRANSLATIONS OF 2nd YEAR STUDENTS MAJORING IN TRANSLATION AND INTERPRETING, FELTE, ULIS IN “TRANSLATION PRACTICE” BY NGUYEN VIET KY AND SUGGESTIONS FOR IMPROVEMENT = Các lỗi thường gặp của sinh viên năm hai ngành biên – phiên dịch, đại học ngoại ngữ, đại học quốc gia hà nội khi dịch Việt – Anh trong giáo trình “thực hành dịch” của Nguyễn Việt Kỳ và giải pháp - ĐHQGHN – Trường Đại học Ngoại ngữ (2020)
From the very first days of their professions, translators have always been entrusted with the role of a communication facilitator who bridges the gap of understanding between people coming from various cultures and speaking different languages. Coming along with this trend, University of Languages and International Studies, VNU also strives to train high-qualified translators to meet the demand of the whole society. With the deep concerns about the situation, the researcher would like to conduct a study entitled “Common errors made by 2nd year students majoring in Translation and Interpreting at FELTE, ULIS, VNU in Translation Practice compiled by Nguyen Viet Ky and suggestions for improvement”. The study aims at identifying common errors made by 2nd year students majoring in Translation and Interpreting in course-book “Translation Practice” compiled by Nguyen Viet Ky. Based on reasons shared by students and experienced teacher, suggestions are offered for the improvement of not only surveyed students but also the next generations of 2nd year students. The major methods and procedures adopted throughout the study include questionnaires, class observations, document observations, diary reports and online interview. A combination of both quantitative and qualitative methods enables the researcher to triangulate the data in order to produce the rich and reliable findings. With this approach, the researcher ensures the validity as well as the reliability of the study. Hopefully, the study proves beneficial to fresh would-be translators at FELTE, ULIS, VNU.